Vehículo robótico con capacidades para verificar el cumplimiento de la Ley 7600 en Costa Rica mediante una plataforma de internet a través de red local” - Moya-Samper, María Beatriz (Instituto Tecnológico de Costa Rica, 2018)
This document shows the development of the control of a robotic vehicle with the possibility of viewing the route through a camera module, through a graphic interface using web pages. In this design a map of the route is also presented, which in turn verifies aspects of Law 7600 regarding ramps and corridors. For all the above, a Raspberry Pi model 3B is used as a central processing module, supported by the Arduino for the interaction with the sensors that measure the variables relevant to the verification of Law 7600, as well as Motor Control HC for the management of the vehicle, on the other hand, is supported by the Raspberry platform as a database and server of the designed website.
Proyecto de Graduación (Licenciatura en Ingeniería Electrónica) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Electrónica, 2018
Keywords: Páginas web; Vehículos; Vehículo autónomo; Research Subject Categories::TECHNOLOGY::Electrical engineering, electronics and photonics